Developing leaders for real proven approaches that deliver impact - Gray, Harry; Gimson, Anne; Cunningham, Ian 1943- (Emerald Publishing, 2022)
Developing Leaders For Real: Proven approaches that deliver impactpresents chapters from international experts analysing approaches to developing leaders that have actually delivered results, capturing how executives at all levels really learn to become better organizational leaders
Keywords: Leadership; Management: leadership & motivation; Business & Economics / Leadership; Electronic books; Aufsatzsammlung